Chemotherapy-Induced Nausea and Vomiting (CINV) with GI Cancer Chemotherapy: Do We Need CINV Risk Score Over and Above Antiemetic Guidelines in Prescribing Antiemetic Regime? - D’Souza, Anita (South Asian J Cancer, 2020)
Background  Various predictive models have been developed which incorporates patient risk factors into the selection of optimal antiemetic therapy, one of which is chemotherapy-induced nausea and vomiting (CINV) risk scoring system developed by Multinational Association of Supportive Care in Cancer (MASCC). Patients and Methods  Consecutive patients with gastrointestinal malignancy who had not received previous chemotherapy were eligible for enrollment in the study if they were scheduled to receive at least one cycle of chemotherapy. The CINV risk assessment tool was used to collect the study data and to assess CINV risk score. Results  Ninety-eight patients fulfilling the eligibility criteria were included in this study, out of which 57% were males, median age was 48 years (range: 28–77). Colorectal cancer (32.7%) was the most common diagnosis followed by gastric cancer (27.6%). Gemcitabine/cisplatin and CAPOX regimen were the most common regimen being administered in 19.4% each. As per MASCC guidelines, 19.4% patients received highly emetogenic chemotherapy, 69.4% moderately emetogenic chemotherapy, while 11.2% received regimen with low emetogenicity. CINV risk module characterized 52% patients to have high risk for CINV, while 48% to have low risk of CINV, thus, 52% had the discrepancy in risk assigned by two methods, and this was statistically significant ( p = 0.025). In subgroup analysis, although patient cohort with acute nausea had no statistically significant discrepancy ( p = 0.123), but statistically significant discrepancy was found in patient cohort with delayed nausea ( p = 0.001), acute ( p = 0.038), and delayed ( p < 0.001) vomiting. Conclusion  A significant percentage of patients who receive chemotherapy continue to experience nausea and vomiting despite receiving antiemetic treatment as per standard guidelines. The study generates a hypothesis for future large randomized studies looking at change in antiemetic prophylaxis based on CINV risk tool, leading to improvement in complete response rates of acute and delayed CINV.